2018
DOI: 10.1002/jper.18-0110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oral microbial corrosion on the surface degradation of dental implant materials

Abstract: TiZr and ZrO dental implant surfaces were not more susceptible to colonization and surface degradation by oral Streptococcus species than commercially pure Ti implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 46 publications
5
22
2
Order By: Relevance
“…As the 50% toxic concentration for DMAE-CB against mouse fibroblasts is comparable to that of Bis-GMA [98], DMAE-CB would not compromise the biocompatibility of its parental adhesive [104]. Like other QAMs, its inhibition of MMPs at 0.5–5 wt% was illustrated [106].…”
Section: Methods To Modify the Bonding Systemmentioning
confidence: 99%
“…As the 50% toxic concentration for DMAE-CB against mouse fibroblasts is comparable to that of Bis-GMA [98], DMAE-CB would not compromise the biocompatibility of its parental adhesive [104]. Like other QAMs, its inhibition of MMPs at 0.5–5 wt% was illustrated [106].…”
Section: Methods To Modify the Bonding Systemmentioning
confidence: 99%
“…TiZr shows the highest corrosion resistance in the presence of cells (cell assays using human lymphoid cells (CEM) and MC3T3-E1 cells) and various electrolytes compared with cp-Ti and Ti6Al4V alloys [18,54]. The evaluation of oral microbial corrosion of dental implant materials revealed that TiZr surfaces had similar behaviors regarding colonization and surface degradation by oral Streptococcus species to those of cp-Ti [55]. The oxides and hydroxides of Ti and Zr have low solubility, acting as passive oxide films with excellent corrosion resistance.…”
Section: Ti50zr Alloy Surface Modificationmentioning
confidence: 99%
“…The fact that the Ti alloy biomaterials are covered with oxides not only inhibits corrosion but also increases biocompatibility. Thus, there is a sustained concern for growing and organizing oxide layers on the surface of these alloys in order to improve the surface properties [55][56][57][58][59][60][61][62][63].…”
Section: Ti50zr Alloy Surface Modificationmentioning
confidence: 99%
“…Once corrosion occurs, it leads to an increased bacterial attachment to the implant, which results in further corrosion. 28 Corrosion has been shown on commercially pure titanium, titanium alloys as well as zirconium 29 . Bacterial attachment can occur within 30 minutes of implant placement, 30 and surface corrosion can occur within 2 days after bacterial attachment 31 …”
Section: How Does Titanium Get Into Tissues?mentioning
confidence: 99%